Digital euro and its taxation: between traceability, privacy, and european fiscal harmonization - Jiménez Vargas, Pedro Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The digital euro is a new form of money being developed by the European Central Bank to adapt to the digital age. This paper explores what it actually is, how it differs from the money we use today (such as cash or bank deposits), and why its impact could be significant. It also analyzes how it may affect taxation from how it should be reported to its implications for VAT, personal income tax, or wealth tax. In addition, it addresses challenges such as privacy protection, payment traceability, and technological management difficulties. Finally, it outlines possible future uses and how tax regulations could be harmonized across Europe.
Keywords: digital euro; taxation; traceability; privacy; european harmonization